Δείκτες ποιότητας και οξειδωτικής σταθερότητας παρθένων ελαιόλαδων Κορωνέικης και Κυπριακής ποικιλίας - Χατζηγιασουμή, Θεόφιλος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Olive oil has been considered important food from the ancient years because of its positive contribution to human health. There are a lot of studies about the olive oil nutritional value and its protective effect against various chronic diseases. Olive oil is characterized by certain quality parameters, their values range between limits established by the International Olive Oil Council. These parameters are used (i) for the classification of olive oils according to their quality, and (ii) for examination for the existence of fraud. In this diploma thesis, quality parameters such as: acidity, peroxide number, indexes K232, K268, ΔΚ have been determined for olive oils of Koroneiki and Cypriot (Ladoelia) variety. Also, the antioxidant (antiradical) capacity of these oils has been determined for the evaluation of the oxidative stability of the oils between the two varieties. Comparison of oils from different districts of the island has been done for the quality parameters and the antioxidant capacity.
Keywords: Olive oil; Acidity; Koroneiki; Ladoelia; Antioxidant capacity; Ελαιόλαδο; Οξύτητα; Κορωνέικη; Λαδοελιά; Αντιοξειδωτική ικανότητα; DPPH